MODELING OF DEEP SOUNDING TEM METHOD FOR MONITORING OF CARBON DIOXIDE (CO2) INJECTION INTO THE RESERVOIR - NUGROHO (NIM : 12313046), GATOT
Monitoring the distribution of CO2 is one of the most important things in CCS sustainability. Seismic method is a geophysical monitoring method which is most used in the CCS monitoring. This research is intended to know the ability of deep sounding TEM method for CCS monitoring. To determine the effect of CO2 presence we have compared TEM data before and after CO2 injection. A baseline survey data was obtained from TEM field measurements in 2013, whereas the TEM data after injection was obtained from simulation using forward modeling results. The inversion modeling is performed by using a SVD damped least squares algorithm. The SVD inversion process is applied to identify the reservoir and the distribution of CO2 in the reservoir after injection. The inversion result of TEM field data shows that reservoir has a low resistivity that is 2 Ωm to 4 Ωm. This reservoir is at a depth of 900 m to 1200 m below the surface. TEM data after injection was obtained from forward modeling with the addition of 5 Ωm resistivity at the reservoir layer as a result of 240 tons CO2 injection after 40 days of injection. Comparison of TEM data before and after injection has indicated a clear presence of CO2. The pattern of TEM data curve after the injection becomes steeper at the center of the measurement. The inversion of TEM data after the injection is still not in accordance with the actual conditions. This is because SVD inversion method damped least square has a solution that is not unique. The local approach used by the method also makes the inversion solution obtained is not in accordance with the actual synthetic model although the calculation result obtained is small enough that less than 5%.